Women, Politics, and Democratic Fiqh: The Existence of Women's Religious Organizations in the 2024 Elections - Kutbuddin Aibak; Ahmad Musonnif (Jurnal Studi Gender dan Anak, 2025)
This study aims to examine the relationship between women's religious organizations and the 2024 election contest from the perspective of fiqh democracy. This is because women's politics in the contemporary context is a necessity to realize justice for women. This study uses qualitative methods to explore the acceleration of women's religious organizations in Tulungagung and Trenggalek Regencies. The collected data is then presented descriptively and analyzed using content analysis through fiqh civilization (civilization jurisprudence). This study finds that (1) Women's religious organizations in Tulungagung and Trenggalek Regencies have demonstrated their strong existence in various aspects of women's participation in the 2024 political arena. (2) The position of women's religious organizations in Tulungagung and Trenggalek Regencies in the 2024 political contest is influenced by various supporting and inhibiting factors. (3) The contribution of women's religious organizations in Tulungagung and Trenggalek Regencies in facing the 2024 political contest can be seen through the fiqh democracy approach, which is the foundation of the women's religious organization movement. [Penelitian ini bertujuan untuk melihat hubungan politik organisasi keagamaan perempuan dalam kontestasi pemilu 2024 perspektif fiqih demokrasi. Hal ini dikarenakan politik perempuan dalam konteks kontemporer menjadi sebuah keniscayaan untuk mewujudkan eksistensi keadilan bagi perempuan. Penelitian ini menggunakan metode kualitatif untuk untuk menggali akselerasi gerakan organisasi keagamaan perempuan di Kabupaten Tulungagung dan Trenggalek. Data yang telah dikumpulkan kemudian dipaparkan secara deskriptif untuk kemudian dianalisis menggunakan metode content analysis melalui fiqih peradaban. Penelitian ini menemukan bahwa (1) Organisasi keagamaan perempuan di Kabupaten Tulungagung dan Trenggalek telah menunjukkan eksistensinya yang kuat dalam berbagai aspek partisipasi perempuan di ranah politik 2024. (2) Posisi organisasi keagamaan perempuan di Kabupaten Tulungagung dan Trenggalek dalam kontestasi politik 2024 dipengaruhi oleh berbagai faktor pendukung dan penghambat. (3) Kontribusi organisasi keagamaan perempuan di Kabupaten Tulungagung dan Trenggalek dalam menghadapi kontestasi politik 2024 dapat dilihat melalui pendekatan fiqih demokrasi yang menjadi landasan gerakan organisasi keagamaan perempuan].